2013
DOI: 10.3171/2013.4.jns122236
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in nontraumatic subdural hematoma

Abstract: Object. Subdural hematoma (SDH) is a common diagnosis in neurosurgical and neurocritical practice. Comprehensive outcome data are lacking for nontraumatic SDH. The authors determined which factors are associated with in-hospital mortality in a large sample of patients with nontraumatic SDH.Methods. Using the Nationwide Inpatient Sample, the authors selected adults who had been hospitalized in the US between 2007 and 2009 and in whom a primary diagnosis of nontraumatic SDH (ICD-9-CM code 432.1) had been made. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…A large epidemiological study reported major organ dysfunction as an independent predictor of mortality. 1,24 Our results showed that the short-term prognosis (acute phase) in elderly patients depends not on comorbidities but on the severity of aSDH, which is expressed by pupillary abnormalities or unconsciousness. 7 Nonetheless, long-term prognosis (3 months' follow-up) in survivors of aSDH also depends on the cumulating comorbidities.…”
Section: Discussionmentioning
confidence: 95%
“…A large epidemiological study reported major organ dysfunction as an independent predictor of mortality. 1,24 Our results showed that the short-term prognosis (acute phase) in elderly patients depends not on comorbidities but on the severity of aSDH, which is expressed by pupillary abnormalities or unconsciousness. 7 Nonetheless, long-term prognosis (3 months' follow-up) in survivors of aSDH also depends on the cumulating comorbidities.…”
Section: Discussionmentioning
confidence: 95%
“…In terms of reoperation, repeat surgery was required in 58 cases (8%), consistent with previous estimates. 4,13 It should be noted that as with comorbidities, many of the adverse events described here could be ascribed more to the natural history of SDH rather than to surgical intervention, and these outcomes could occur more frequently without intervention. The order of causation-that is, which comes first-is unknown, but the associations are present.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…4,10 However, nontraumatic SDH in this context does not represent true spontaneous hemorrhage, but rather an SDH without a documented known injury. Hence, despite the difference in coding, these patients were considered together in this study.…”
Section: Patient Populationmentioning
confidence: 99%
See 2 more Smart Citations